Essential oil from Cymbopogon nardus and repellant activity against Aedes aegypti - Ni Luh Arpiwi; I Ketut MUksin; Ni Luh Kartini (Society for Indonesian Biodiversity, 2020)
Abstract. Arpiwi NL, Muksin IK, Kartini NL. 2020. Essential oil from Cymbopogon nardus and repellant activity against Aedes aegypti. Biodiversitas 21: 3873-3878. Cymbopogon nardus (L.) Rendle is an aromatic grass from the Poaceae family that produces essential oil mainly in the leaves. The essential oil from C. nardus is known as citronella oil has repellent activity. This research aimed to quantify the oil content of C. nardus leaves, to analyze the essential oil quality, to analyze the repellent activity of lotion with different concentrations of citronella oil against Aedes aegypti, and to examine the quality of formulated lotions. The oil was extracted from leaves using steam distillation, and the quality was examined according to the Indonesian National Standard. The citronella oil was formulated into a lotion with five concentrations (0, 2, 3, 4, 5% w/w). Repellent activity of the lotions against Ae. aegypti was tested using screened cage test method under laboratory conditions. Lotion quality was analyzed for pH, viscosity, homogeneity, and sensorial assessments. The result showed that the oil yield of C. nardus leaves was 0.9% w/w. The color of the oil was pale yellow, specific weight was 0.8819, the refraction index was 1.464, total geraniol was 72.71%, citronellal content was 49.14%, and solubility in 80% alcohol 1:2 was clear. The repellent activity of lotions with citronella oil was concentration-dependent, where a concentration of 5% gave the highest protection. The quality of formulated lotions met the standard and the lotions were nonirritant.